Unselective Overimitators: The Evolutionary Implications of Children's Indiscriminate Copying of Successful and Prestigious Models. Issue 3 (May 2016) - Chudek, Maciej; Baron, Andrew S.; Birch, Susan
Abstract : Children are both shrewd about whom to copy—they selectively learn from certain adults—and overimitators—they copy adults' obviously superfluous actions. Is overimitation also selective? Does selectivity change with age? In two experiments, 161 two‐ to seven‐year‐old children saw videos of one adult receiving better payoffs or more bystander attention than another. Children then watched the adults perform unnecessary actions on novel transparent devices. Children preferred the adult who received greater payoffs or bystander attention when asked questions like "Who do you think is smarter?" but overimitated both adults' unnecessary actions equally. Although older children overimitated more, unselectivity was consistent across ages. This pattern hints at a plausible adaptive function of overimitation: acquiring rarely demonstrated behaviors by practising them immediately.